Adapt or die—Response of large herbivores to environmental changes in Europe during the Holocene. (12th July 2019) - Hofman‐Kamińska, Emilia; Bocherens, Hervé; Drucker, Dorothée G.; Fyfe, Ralph M.; Gumiński, Witold; Makowiecki, Daniel; Pacher, Martina; Piličiauskienė, Giedrė; Samojlik, Tomasz; Woodbridge, Jessie; Kowalczyk, Rafał
Abstract: Climate warming and human landscape transformation during the Holocene resulted in environmental changes for wild animals. The last remnants of the European Pleistocene megafauna that survived into the Holocene were particularly vulnerable to changes in habitat. To track the response of habitat use and foraging of large herbivores to natural and anthropogenic changes in environmental conditions during the Holocene, we investigated carbon ( δ 13 C) and nitrogen ( δ 15 N) stable isotope composition in bone collagen of moose ( Alces alces ), European bison ( Bison bonasus ) and aurochs ( Bos primigenius ) in Central and Eastern Europe. We found strong variations in isotope compositions in the studied species throughout the Holocene and diverse responses to changing environmental conditions. All three species showed significant changes in their δ 13 C values reflecting a shift of foraging habitats from more open in the Early and pre‐Neolithic Holocene to more forest during the Neolithic and Late Holocene. This shift was strongest in European bison, suggesting higher plasticity, more limited in moose, and the least in aurochs. Significant increases of δ 15 N values in European bison and moose are evidence of a diet change towards more grazing, but may also reflect increased nitrogen in soils following deglaciation and global temperature increases. Among the factors explaining the observed isotope variations were time (age of samples), longitude and elevation in European bison, and time, longitude and forest cover in aurochs. None of the analysed factors explained isotope variations in moose. Our results demonstrate the strong influence of natural (forest expansion) and anthropogenic (deforestation and human pressure) changes on the foraging ecology of large herbivores, with forests playing a major role as a refugial habitat since the Neolithic, particularly for European bison and aurochs. We propose that high flexibility in foraging strategy was the key for survival of large herbivores in the changing environmental conditions of the Holocene. Abstract : The Holocene has been an epoch of highly dynamic environmental changes. We analysed isotopic signatures in bone collagen of the three largest European herbivores that survived the Pleistocene/Holocene transition to determine the influence of natural and anthropogenic factors on habitat use and diet. European bison, aurochs and moose shifted from more open habitats in the Early (pre‐Neolithic) Holocene to forests during the Neolithic and Late Holocene in response first to forest expansion and later because of human impact. Our results show that foraging plasticity was the key for survival of large herbivores in the changing environmental conditions of the Holocene.